CsgE is a curli secretion specificity factor that prevents amyloid fiber assembly - Nenninger, Ashley A. (2011)
Curli are extracellular amyloid fibers produced by Escherichia coli that are critical for biofilm formation and adhesion to biotic and abiotic surfaces. CsgA and CsgB are the major and minor curli subunits, respectively, while CsgE, CsgF, and CsgG direct the extracellular localization and assembly of curli subunits into fibers. The secretion and stability of CsgA and CsgB are dependent on the outer membrane lipoprotein CsgG. Here, we identified functional interactions between CsgG and CsgE during curli secretion. We discovered that CsgG overexpression restored curli production to a csgE strain under curli-inducing conditions. In antibiotic sensitivity and protein secretion assays, CsgG expression alone allowed translocation of erythromycin and small periplasmic proteins across the outer membrane. Co-expression of CsgE with CsgG blocked non-specific protein and antibiotic passage across the outer membrane. However, CsgE did not block secretion of proteins containing a 22 amino acid putative outer membrane secretion signal of CsgA (A22). Finally, using purified proteins, we found that CsgE prohibited the self-assembly of CsgA into amyloid fibers. Collectively, these data indicate that CsgE provides substrate specificity to the curli secretion pore CsgG, and acts directly on the secretion substrate CsgA to prevent premature subunit assembly.